Simulation Model of Automated Peat Briquetting Press Drive - A. A. Marozka; Y. N. Petrenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2012)
The paper presents the developed fully functional simulation model of an automated peat briquetting press drive. The given model makes it possible to reduce financial and time costs while developing, designing and operating a double-stamp peat briquetting press drive.